The impact of global value chain position on emerging industrial cluster innovation efficiency in China - Xu, Yan; Hamzah, Hanny Zurina; Hook, Law Siong (HRMARS, 2024)
With the increasingly frequent international interaction, economic globalization has become the main trend of social development. The position of division of labor in global value chains greatly affects the income share of a country participating in international economic activities. Despite remarkably enhance in China's GVC position of its primary industries, manufacturing, and services, demonstrating a trend of "catching up," there remains a considerable gap in emerging industries. This paper studies the problems existing in the emerging industry cluster at this stage, such as the lack of technological innovation, the imbalance of regional industrial cluster layout, and the defects of financial policy system. We analyze the mechanism and impact of GVC position on the industrial cluster innovation efficiency. The conclusion is that higher GVC position can improve innovation efficiency, and the influence of upstream or downstream position on innovation efficiency is different. In addition, the influence is dynamic. Based on this analysis, we put forward suggestions for enhancing GVC position and targeted to provide a theoretical reference for the emerging industrial cluster innovation efficiency improvements.